A luminescent Zn-MOF exhibiting high water stability: selective detection of Cr(VI) ion and treatment activity on sepsis. Issue 1 (1st January 2021) - Wan, Ying; Chen, Xu-Mei; Zhang, Qian; Jiang, Hong-Biao; Feng, Ran
ABSTRACT: A fresh metal-organic framework (MOF) based on the Zn ions as the metal ions has been prepared via the solvothermal method, and its chemical formula is [Zn(byia)(DMF)]·1.5DMF·7H2 O (1, byia =  5-(benzimidazol-2-yl) isophthalic acid). It is worth noting that the compound 1 has excellent water stability (which can be maintained in the water for at least a month). Most fascinating, in water, the compound 1 exhibits the strong blue luminescence, which can only be selectively quenched via the contaminant of the Cr2 O7 2– ion. The selective luminescence quenching with low limits of detection and high values of K sv proved its better sensing property, which can be compared with the contemporary materials. To development new strategy for the sepsis treatment, the biological activity and mechanism of the compound was explored. Firstly, the ELIA detection was performed in this experiment to assess the inhibition of compound against inflammatory factor storm during sepsis. Then, the inflammatory response in the immune cells was assessed by real time RT-PCR.